Insights Into the Role of Bmi‐1 Deregulation in Promoting Stemness and Therapy Resistance in Glioblastoma: A Narrative Review - Shaalan, Fatima; Ballout, Nissrine; Chamoun, Wafaa Takash (Cancer medicine (Malden, MA), 2025)
ABSTRACT Background Glioblastoma (GBM) is the most common primary brain tumor in adults and has a median survival of less than 15 months. Advancements in the field of epigenetics have expanded our understanding of cancer biology and helped explain the molecular heterogeneity of these tumors. B‐cell‐specific Moloney murine leukemia virus insertion site‐1 (Bmi‐1) is a member of the highly conserved polycomb group (PcG) protein family that acts as a transcriptional repressor of multiple genes, including those that determine cell proliferation and differentiation. We hereby aim to explore the specific involvement of Bmi‐1 in glioma pathogenesis. Methods A comprehensive narrative review was employed using “PubMed”. Articles were screened for relevance specific keywords and medical subject headings (MeSH) terms related to the topic combined with Boolean operators (AND, OR). Keywords and MeSH terms included the following: “glioma”, “polycomb repressive complex 1”, and “Bmi1”. Results In GBMs, several reports have shown that Bmi‐1 is overexpressed and might serve as a prognostic biomarker. We find that Bmi‐1 participates in regulating the gene expression and chromatin structure of several tumor suppressor genes or cell cycle inhibitors. Bmi‐1 has a critical role in modulating the tumor microenvironment to support the plasticity of GBM stem cells.We explore Bmi‐1's involvement in maintaining glioma stem cell (GSC) proliferation and senescence evasion upon regulating the chromatin structure of several tumor suppressor genes, cell cycle inhibitors, or stem cell genes in tumor cells. Additionally, we analyze Bmi‐1's involvement in modulating the DNA repair machinery or activating anti‐apoptotic pathways to confer therapy resistance. Importantly, our research discusses the importance of targeting Bmi‐1 that could be a promising therapeutic target for GBM treatment. Bmi‐1 activates and interacts with NF‐κB to promote angiogenesis and invasion, regulates the INK4a‐ARF locus, and interacts with various microRNAs to influence tumor progression and proliferation. In addition, Bmi‐1 confers radioresistance and chemotherapy by promoting cell senescence evasion and DNA repair. Conclusion Bmi‐1 regulates self‐renewal, proliferation, and differentiation of GBM cells, promoting stemness and therapy resistance. Targeting Bmi‐1 could be a promising novel therapeutic strategy for GBM treatment.